THE RELATIONSHIP BETWEEN CIVIC FACTORS AND THE MIDDLE PROFICIENCY LEVEL OF CIVIC KNOWLEDGE - Čekse, Ireta; Alksnis, Reinis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This study explores the relationship between civic and citizenship factors and the middle proficiency level of students’ civic knowledge in the Baltic countries: Estonia, Latvia and Lithuania. The study uses large scale data from the IEA’s International Civic and Citizenship Education Study (ICCS) 2016. According to ICCS 2016, 39% of students from the three Baltic countries and only 26% of students from the Nordic countries had a middle proficiency level of civic knowledge. This middle proficiency level is the largest group in comparison to other levels. Therefore, the study aims to recognise the differences between the highest and lowest achievements in the middle proficiency level of civic knowledge and to examine the relationship between factors such as background, values, behaviour, citizenship activities and attitudes. Multivariable linear regression was used for the data analysis, creating several models. The results show that there are different factors associated with the highest and lowest achievements in the middle proficiency level. For example, the results indicate that students with a lower proficiency level participated in illegal protest activities more often and had lower critical thinking skills. Moreover, the research investigates differences inside the middle proficiency level of civic knowledge and between the lowest middle-level students and students from the lower level of civic knowledge.